Human Resource Management - Jyothi, P. (Oxford University Press, 2006)
Human Resource Management is a comprehensive textbook that is specially designed to meet the needs of students pursuing a Master's in Business Administration/ Postgraduate Diploma in Management. Users will find this book highly useful for its coverage of the role of the knowledge worker and the human resources manager, the impact of globalization on human resource practices, career management and development, the interplay of perspectives on industrial relations and human resource management, and human resource accounting and audit procedures. Caselets, tables, flow charts, and diagrams are provided throughout the text